The Effect Of Probing-Prompting Learning Model On Students’ Interest And Learning Outcomes Of Mathematics In Grade IV SDN Tejo 1 Mojoagung Jombang - Santika Putri Dwi Anhar; Muhammad Nuruddin (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2022)
This study aims (1) to determine student learning outcomes on mathematics subjects with the influence of the probing-prompting learning model for fourth grade students. (2) to determine student responses to interest and student learning outcomes in mathematics with the influence of class IV probing-prompting learning model. (3) to explain whether or not there is an effect of the probing-prompting learning model on the interest and learning outcomes of fourth grade mathematics students at SDN Tejo 1 Mojoagung. This research was conducted at SDN Tejo 1 Mojoagung Jombang in April - May, 2021/2022 academic year. The research approach used in this research is quantitative, the type of research is descriptive research. The number of samples in this study amounted to 24 students in class IVB SDN Tejo 1 Mojoagung. In calculating the data analysis, the researcher used descriptive statistics and sample paired statistics. Data collection techniques in the form of tests and questionnaires as well as documentation. The results of data calculations using sample paired statistics state the results are sig2-talled) or the significance shows the results of 0.00 which means <0.05. So it can be concluded that there is a significant influence on the learning process using the probing-prompting learning model on the interest and learning outcomes of fourth grade students in mathematics at SDN Tejo 1. Based on the results of the conclusions above, suggestions are made for teachers to use to apply learning with the Probing-prompting learning model in mathematics lessons on flat shapes in grade IV. Because the results of this study indicate the probing-prompting learning model has an effect on students' interests and learning outcomes.